Correlates of mental health of people living with HIV co-infected with SARS-CoV-2: findings from the COVIDHIV study in France - Yaya, Issifou; Amboise, Yvenie; Roucoux, Guillaume; Yombo-Kokule, Lisa; Marcellin, Fabienne; Duvivier, Claudine; Lacombe, Karine; Griffith, James W.; Préau, Marie; Cheret, Antoine; Duracinsky, Martin (Frontiers in Psychiatry, 2025)
BackgroundThe COVID-19 pandemic has severely affected vulnerable populations, especially individuals living with HIV/AIDS (PLWHA). The convergence of HIV/AIDS and COVID-19 presents unique challenges, exacerbating existing health concerns and magnifying the strain on individuals already grappling with compromised immune systems. This study aimed to investigate the mental well-being repercussions faced by PLWHA co-infected with SARS-CoV-2 in France.MethodsCOVIDHIV is a French multicenter cohort of PLWHA co-infected with SARS-CoV-2, which collected sociodemographic, clinical, and mental health data. Anxiety and depression symptoms and post-traumatic stress disorder (PTSD) were assessed by the Hospital Anxiety and Depression Scale (HADS) and the PTSD Checklist (PCL-S), respectively. Multivariable logistic regression was performed to identify factors associated with mental health outcomes at inclusion in the cohort.ResultsOf the 397 participants included, 64.7% were male. The mean age was 51.6 (± 11.8) years. The prevalence of mental health outcomes was 33.5% ([95%CI: 28.5-39.0%]) for anxiety, 21.0% ([16.8-25.9%]) for depression, and 12.2% ([8.9-16.5%]) for PTSD. In multivariable regression adjusted for sex, COVID-19 wave and duration between COVID-19 confirmation and enrolment, age (adjusted odds-ratio (aOR): 0.97 [0.95-0.99]), being professionally active (0.43 [0.25-0.75]), and the number of self-reported symptoms (1.17 [1.11-1.24]) were associated with anxiety. Being professionally active (0.34 [0.18-0.65]), living in a couple (0.52 [0.20-0.98]), number of self-reported symptoms (1.15 [1.08-1.22]), and hospitalization for COVID-19 (3.35 [1.34-8.33]) were associated with depression. The number of self-reported symptoms (1.27 [1.16-1.41]), psychiatric disorders (4.04 [1.48-11.11]), and perceived vulnerability to COVID-19 (4.53 [1.69-14.60]) were associated with PTSD.ConclusionThe mental health is a challenging issue among the participants and needs to be closely monitored among people already affected by a chronic disease such as HIV. The findings underscore the urgent need for targeted support and interventions tailored to address the mental health needs of PLWHA facing the dual burden of HIV/AIDS and COVID-19.